A Study on Socio-Economic Status and Psychological Characteristics of Judo Players: Understanding the Relationship between Socio-Economic Factors, Psychological Traits, and Performance in Judo (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper we will discuss about physical education identified with man's fundamental exercises, for example, strolling, running, bouncing, tossing and so forth and every one of these exercises are composed as play, game and sports. Play is a pleasant encounter getting from conduct which is self-started as per individual objectives or expressive motivations. It endures all scopes of developments. Its principles are unconstrained. It has start of a transient succession however no foreordained consummation. It brings about no substantial result triumph a prize sports is a human action which includes explicit regulatory association and authentic back ground of rules which characterize the goal and farthest point the example of human conduct. It includes rivalry or challenge and a positive outcome fundamentally dictated by physical skills. Games are exercises with an endless supply of time space, territory and the guidelines that characterize the goal and point of confinement the patter of human conduct. The result of game and sports is to decide a champ or a failure by totaling unbiased scored achievement.